![Default Avatar](https://respostas.mx/applications/dashboard/design/images/defaulticon.png)
sacji
sacji
About
- Username
- sacji
- Joined
- Visits
- 0
- Last Active
- Roles
- Member
Comments
-
((c-2)*(c))/2=35 (c-2)*(c)=70 (c^2)-2c=70 (c^2)-2c-70=0 a=1 b=-2 c=-70 Y ya de ahi lo resuelves por formula general porque no pude poner los signos..
-
((c-2)*(c))/2=35 (c-2)*(c)=70 (c^2)-2c=70 (c^2)-2c-70=0 a=1 b=-2 c=-70 Y ya de ahi lo resuelves por formula general porque no pude poner los signos..
-
((c-2)*(c))/2=35 (c-2)*(c)=70 (c^2)-2c=70 (c^2)-2c-70=0 a=1 b=-2 c=-70 Y ya de ahi lo resuelves por formula general porque no pude poner los signos..